A BALIMONT Multi-Strain Probiotic Platform for Enhancing IgA-Associated Mucosal Immunity: Formulation Optimization and Preclinical Evaluation - Ziraoui, Anas; Sinclair, Arabella; Cole, Jaxon (International Journal of Agriculture and Food Sciences Research, 2026)
Background: Secretory immunoglobulin A (sIgA) is central to epithelial defense and host-microbe homeostasis. Probiotic products positioned for immune support frequently underperform when strain selection, storage resilience, and intestinal delivery are not optimized. Methods: We reorganized a formulation-development and preclinical dataset describing the BALIMONT immune-support platform and integrated representative published evidence on IgA-oriented probiotic, postbiotic, and prebiotic interventions. The BALIMONT system combined Bifidobacterium bifidum ATCC 29521, Bifidobacterium longum DSM 20219, and Lacticaseibacillus rhamnosus ATCC 7469 with a heat-inactivated Lactococcus lactis-derived postbiotic fraction, a prebiotic support matrix, and staged protective encapsulation. Results: Within the development dataset, the 2:2:2 tri-strain ratio yielded the strongest in vitro response, with secretory IgA of 21.35 μg/mL and probiotic proliferation of 5.62-fold. A 1:1 postbiotic-to-probiotic cell-count ratio maximized both IgA induction and 30-day viable-count retention. In mice, the 200 mg/kg BALIMONT group exceeded a same-category comparator by 39.68% for serum total IgA, 56.52% for intestinal mucosal sIgA, and 53.01% for fecal sIgA. Viable-count retention remained 86.72% after 6 months at 25°C/60% RH. Published clinical and translational evidence further supports the biological plausibility of IgA-associated mucosal benefits from probiotic and synbiotic strategies. Conclusions: The BALIMONT platform can be interpreted as a rationally balanced probiotic-postbiotic system in which strain synergy, postbiotic complementation, prebiotic support, and staged delivery converge on IgA-associated mucosal immunity. These findings support continued translational development and justify subsequent human validation.